Social acceptance towards person with mobility impairment participation in nature-based recreation activities based on the theory of planned behaviour - Ramlan, Mohd. Aswad; Yee, New Soo; Zainal Abidin, Zulkhairi Azizi (Taylor and Francis Group, 2023)
Attitude, norm and perceived behaviour control were theorized as important concepts influencing intention. Understanding these concepts toward persons with disabilities (PWDs) simultaneously is essential in developing acceptance and achieving an inclusive society. This study utilizes the Theory of Planned Behaviour to gain insights that could help promote public acceptance towards the participation of people with mobility impairment (PWMI) in nature-based recreation. An online survey was distributed to Malaysian respondents using a non-random sampling approach (n = 275). Based on descriptive analysis, the Malaysian sample has a slightly positive attitude (M = 3.31), low subjective norm (M = 1.89) and slightly positive in their perceived behaviour control in assisting PWMI (M = 3.58). Regression analyses revealed norm had the most frequent significant interactions and had the strongest relationships relative to attitude and perceived control variables. Lack of perceived control affects respondent intention to help according to different types of recreational activities. These findings present a serious need to promote acceptance by improving public attitude and perceived control, as well as breaking any normative barriers. Future research could extend the current findings by investigating public acceptance of different types of disabilities and employing a more robust sampling approach.